Assessment and improvement of hydraulic disinfection efficiency of a live small drinking water system in South Africa - Baker, Jessica L., author; Venayagamoorthy, S. Karan, advisor; Niemann, Jeffrey, committee member; Leisz, Stephen, committee member (Colorado State University. Libraries, 2018)
Since the implementation of chlorination, the most common method of water disinfection, diseases such as Cholera, Typhoid Fever, and Dysentery have been essentially eliminated in the U.S. and other industrialized countries (WHO 2017). However, these nations still experience challenges in meeting drinking water standards. In 2009, the Colorado Department of Public Health and Environment contracted Colorado State University (CSU)'s Department of Civil and Environmental Engineering to address the poor hydraulic disinfection efficiency of contact tanks of small-scale drinking water systems. From this research, the Baffling Factor Guidance Manual (2014) was published, which presents innovative modifications proven to increase the hydraulic disinfection efficiency of small-scale contact tanks. The proposed innovative technology has the potential to have a significant positive impact in developing nations since at least 2 billion people worldwide use a drinking water source that is contaminated with feces (WHO 2017). Historical experience suggests that simply transporting a technology does not necessarily equate to long-lasting impact, but how that technology is transferred is critical to its sustainability. A successful solution to the need for disinfected water must be holistic, taking into consideration culture, law, politics, economics, environment, etc. The focus of this thesis is to investigate further the application of the innovative contact tank modifications of an inlet manifold and random packing material (RPM) on live systems. A case study was conducted on a small waterworks in the rural town of Rosetta, KwaZulu-Natal, South Africa, in collaboration with Umgeni Water. Physical tracer tests were conducted on a 10,000L cylindrical tank acting as the contact chamber to assess the hydraulic disinfection efficiency in terms of baffling factor (BF), before and after the installation of a 4-way inlet manifold modification. This modification resulted in a 37% improvement in the BF, increasing the contact time (CT), an important aspect of disinfection, in the cylindrical contact tank from 8.4 min-mg/L to 11.0 min-mg/L. In addition to the international case study, a pilot study was conducted at CSU to address the biofilm formation concerns of the innovative use of random packing material (RPM) in contact tanks. Preliminary results support the hypothesis that the presence of a disinfectant in the contact tank, though in the process of disinfecting the water, would mitigate the growth of a biofilm on the RPM.
Keywords: contact time; efficiency; baffling factor; hydraulic; disinfection